Structurer à l’étape de la retouche - Gaëlle Pentier (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The pictorial creation is in constant mutation in its ways of expression and materials. This evolution gives rise to new problematic which can challenge the current retouching methods.The structural retouching consists in reintegrating the colors and the physical relief of a lacuna in one step. In this review we will evaluate if this technique can be used as an alternative to the current retouching techniques. Moreover we will identify the different materials which can be used to create a bodied retouching in agreement with the requirements of conservation.